A professional development framework for teaching mathematics meaningfully with technology in Namibian secondary schools: A design-based research study - Kanandjebo, Leena Ngonyofi (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.